Pemetaan Potensi Wisata Pulau Ma menggunakan Sistem Informasi Geografi - Rauf, Ichsan; Conoras, Amrin; Kusnadi; Basri, Ardi; Amelia, Risky (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
The government has established the tourism sector as the leading sector of the national economy. This means that the tourism sector is a motor thet can drive economic growth in a region. Maitara Island has considerable potential to be developed as a tourist village in North Maluku Province, especially since Maitara Island has long been known to the people of Indonesai through the 1000 rupiah denomination. Information related to tourist objects in an area is very important for tourists to visit, while for stakeholders this information is useful in developing the tourism. This research was conducted to inventory places on Maitara Island that have the potential to be developed as tourist destinations and to map these potentials based on geographic information systems. The object inventory method is carried out using GPS and camera devices as documentation, while the mapping of these objects is carried out using the ArcGIS application. The results of the inventory show that Maitra Island has natural and cultural landscapes that can be developed as maritime tourism, sports tourism, cultural tourism, and science tourism.